2016
DOI: 10.1155/2016/1654938
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Pediatric Formulations to Treat Children with HIV

Abstract: Over 3.2 million children worldwide are infected with HIV, but only 24% of these children receive antiretroviral therapy (ART). ART adherence among children is a crucial part of managing human-immunodeficiency virus (HIV) infection and extending the life and health of infected children. Important causes of poor adherence are formulation- and regimen-specific properties, including poor palatability, large pill burden, short dosing intervals, and the complex storage and transportation of drugs. This review aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 70 publications
2
60
0
4
Order By: Relevance
“…The relatively high caregiver acceptability (81%) and preference demonstrated by the caregivers’ responses can be mainly attributed to the improved tolerability of the drug by the children, perhaps as function of the pellets’ improved palatability over the syrup formulation and the ability to easily co‐administer it with soft foods such as porridge. These findings are supported by various studies , which report that these features of a medication are key factors which influence acceptability by caregivers. Although no direct comparisons were made between the pellets and syrup formulation in this study, the findings support the argument for solid formulations being more acceptable to caregivers of young children than what may be seen to be a more obvious solution of syrup formulations.…”
Section: Resultssupporting
confidence: 71%
“…The relatively high caregiver acceptability (81%) and preference demonstrated by the caregivers’ responses can be mainly attributed to the improved tolerability of the drug by the children, perhaps as function of the pellets’ improved palatability over the syrup formulation and the ability to easily co‐administer it with soft foods such as porridge. These findings are supported by various studies , which report that these features of a medication are key factors which influence acceptability by caregivers. Although no direct comparisons were made between the pellets and syrup formulation in this study, the findings support the argument for solid formulations being more acceptable to caregivers of young children than what may be seen to be a more obvious solution of syrup formulations.…”
Section: Resultssupporting
confidence: 71%
“…Without treatment, more than 50% of HIV-infected infants die before their second birthday 74 . The time is ripe to focus on personal variation to the taste of their medicine 75 since a drug, no matter how powerful, is ineffective when the child rejects it 71 . By taking the perspective of precision medicine that “nobody is average”, a greater understanding of the genetic and phenotypic variation underlying the flavor of a given medicine may inform the clinical care of the patient and lead to molecular targets to improve palatability.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid ART formulations are often bitter and poorly tolerated; 29 their cost is up to four times higher than tablets; and the bulk and weight of multiple months of liquid ART makes them conspicuous and difficult to transport and store. 30 Dosing of liquid formulations require medication dispensers with markings, which may present as a challenge for caregivers with poor vision or lack of education.…”
Section: Art Adherencementioning
confidence: 99%
“…30 In order to avoid liquid formulations some caregivers report crushing tablets or opening capsules in order to sprinkle them over food, which may result in inadequate dosing of ART. 29 Gastrostomy tubes have been used to provide a more reliable route of administration. Studies showed that gastrostomy tubes were associated with improved adherence in young children and decreased the time required to administer ART.…”
Section: Art Adherencementioning
confidence: 99%